Adherence to dietary supplementation with menaquinone-7, a vitamin K2 analogue - Liv M Vossen; Leon J Schurgers; Claudia de Haan; Abraham A Kroon; Peter W de Leeuw (Exploration of Medicine)
Aim: The VitaK-CAC (vitamin K-coronary artery calcification) trial is a double-blind, randomized, placebo-controlled trial in patients with pre-existent CAC who were treated for two years with either placebo or the vitamin K2-analogue menaquinone-7 (MK-7). The purpose of the present analysis of the VitaK-CAC trial was to assess the degree of adherence to supplementation with MK-7 during the implementation and persistence phases. Methods: We estimated adherence in three different ways: 1) by pill counts, 2) by measuring plasma levels of MK-7, and 3) by measuring plasma levels of dephosphorylated, uncarboxylated matrix Gla-protein (dp-ucMGP), a marker of the functional bioactivity of vitamin K. Results: Estimated adherence based on pill counts was 90%, but it was lower (80%) when plasma levels of vitamin MK-7 were taken as reference. Changes in dp-ucMGP appeared not to be independent from those of MK-7. Conclusions: We conclude that none of the three methods that we applied in our study is absolutely reliable to estimate adherence to supplementation with MK-7. Yet, the measurement of MK-7 levels provides the best information (the study has been registered at clinicaltrials.gov as NCT01002157).